2013
DOI: 10.1186/1755-8794-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Genetic lineages of undifferentiated-type gastric carcinomas analysed by unsupervised clustering of genomic DNA microarray data

Abstract: BackgroundIt is suspected that early gastric carcinoma (GC) is a dormant variant that rarely progresses to advanced GC. We demonstrated that the dormant and aggressive variants of tubular adenocarcinomas (TUBs) of the stomach are characterized by loss of MYC and gain of TP53 and gain of MYC and/or loss of TP53, respectively. The aim of this study is to determine whether this is also the case in undifferentiated-type GCs (UGCs) of different genetic lineages: one with a layered structure (LS+), derived from earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…85,86 Many studies reported that a significant increase in MYC copy number can be detected in the carcinogenic process of GC and in gastric cell lines. [87][88][89][90][91][92] The amplification of MYC has also been suggested with independent prognostic value on overall survival. 93 In addition, MYC CNVs has a tight connection with the clinicopathological features of GC.…”
Section: Chromosomementioning
confidence: 99%
“…85,86 Many studies reported that a significant increase in MYC copy number can be detected in the carcinogenic process of GC and in gastric cell lines. [87][88][89][90][91][92] The amplification of MYC has also been suggested with independent prognostic value on overall survival. 93 In addition, MYC CNVs has a tight connection with the clinicopathological features of GC.…”
Section: Chromosomementioning
confidence: 99%
“…Given that samples from the same tumor might share random generation of gene CNAs and tissue environmental selection, different parts of a tumor might have similar CNA profiles in the presence of a common carcinogenetic process [8, 9]. CNA profiles that have a low noise level could satisfy this internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…For smaller gene numbers, the reproducibility of clustering analysis becomes lower, but gene size is larger. Thus, for determining optimal gene size and number, the clustering analysis was repeatedly performed using the Clustering 3.0 (v1.52) software and TreeView (v1.1.6r2) [8, 9]. The unsupervised clustering analysis was based on genomic copy-number profile resemblance, and complete linkage and uncentered correlation distance were applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the CNA profile of clinically detectable breast cancer may already include information enough for outcome prediction. In our previous gastric cancer studies, we classified the samples based on their CNA profiles using unsupervised hierarchical cluster analyses and demonstrated that nearly all early cancer of the undifferentiated type can become advanced [19], whereas approximately 80% of noninvasive neoplasms of the differentiated type showed a lineage distinct from advanced cancers [20]. …”
Section: Introductionmentioning
confidence: 99%